Periodontics, Implantology, and Prosthodontics Integrated: The Zenith-Driven Rehabilitation - Frizzera, Fausto; Tonetto, Mateus; Cabral, Guilherme; Shibli, Jamil Awad; Marcantonio, Elcio [UNESP] (Hindawi Ltd, 2017)
A customized treatment plan is important to reach results that will satisfy the patient providing esthetics, function, and long-term stability. This type of oral rehabilitation requires professionals from different dental specialties where communication is a major key point. Digital Smile Design allows the practitioners to plan and discuss the patient's condition to establish the proper treatment plan, which must be driven by the desired zenith position. The ideal gingival position will guide the professionals and determine the need to perform surgical procedures or orthodontic movement before placing the final restorations. In this article, the zenith-driven concept is discussed and a challenging case is presented with 4-year follow-up where tooth extraction, immediate implant placement, bone regeneration, and a connective tissue graft were performed.